The association of ultra-processed food intake on age-related muscle conditions: a systematic review and dose–response meta-analysis with meta-regression - Mohammad Ali Hojjati Kermani; Farhang Hameed Awlqadr; Sepide Talebi; Sanaz Mehrabani; Donny M. Camera; Reza Bagheri; Fariborz Poorbaferani; Seyed Mojtaba Ghoreishy; Parsa Amirian; Mahsa Zarpoosh; Sajjad Moradi (Journal of Health, Population and Nutrition)
Abstract Objectives Chronic excessive intake of ultra-processed foods (UPFs) has been linked to various metabolic conditions; however, its impact on skeletal muscle mass and function in older adults remains unclear. Therefore, we conducted this study to examine the association between UPF intake and age-related muscle outcomes, including frailty, sarcopenia, low muscle mass (LMM), and/or low muscle strength (LMS). Methods A systematic search was conducted in ISI Web of Science, LILACS, PubMed/MEDLINE, and Scopus without restrictions up to November 1, 2024. Relative risks (RRs) and 95% confidence intervals (CIs) were pooled using a random-effects model. Study quality and the presence of publication bias were assessed using the Newcastle–Ottawa Scale, Egger’s regression asymmetry test, and Begg’s rank correlation test. Results Data from 29 studies were included. Cohort studies showed that higher UPF intake was significantly associated with an increased risk of frailty (RR = 1.40; 95% CI 1.25–1.58; I2 = 83.0%; p < 0.001; n = 11), but not with LMS. In contrast, cross-sectional studies indicated that higher UPF intake was significantly associated with an increased risk of LMS (RR = 1.13; 95% CI 1.06–1.20; I2 = 0.0%; p < 0.001; n = 5), but not with frailty, sarcopenia, or LMM. Furthermore, a 100 g increase in UPF intake was associated with a 3% higher risk of frailty (RR = 1.03; 95% CI 1.01–1.06; I2 = 85.1%; p = 0.016; n = 5). Non-linear dose–response analysis showed a positive linear association between UPF intake and frailty risk (P_non-linearity = 0.807; P_dose-response < 0.001; n = 5). Conclusion Higher UPF intake was associated with an increased risk of frailty in cohort studies and with low muscle strength in cross-sectional studies. These findings suggest that regular consumption of UPFs may negatively affect muscle health, potentially impairing quality of life and independence in older adults.